FRI0004 Granulocyte macrophage colony stimulating factor is secreted at higher levels from stimulated monocyte-derived macrophages from patients with enthesitis related arthritis and is significantly enhanced by the unfolded protein response. (12th June 2018) - Fisher, C.; Eleftheriou, D.; Sen, D.; Ioannou, Y.
Abstract : Background: Enthesitis related arthritis (ERA) is a subtype of juvenile idiopathic arthritis exhibiting many similarities to the adult spondyloarthropathies (SpA). The innate immune system and intracellular stress responses, including the unfolded protein response (UPR), have been implicated in the pathogenesis of SpA. Granulocyte macrophage colony stimulating factor (GMCSF), as well as being a haemopoietic growth factor, plays a central role in regulating innate immunity and has recently been implicated in the pathogenesis of SpA 1 but has not been studied in ERA. Objectives: To compare levels of GMCSF produced by monocyte-derived macrophages (MDMs) from patients with ERA and healthy controls and to observe the effect of inducing the UPR on those levels. Methods: Peripheral blood monocytes were isolated from 39 patients with ERA (68% HLA B27 positive, 84% male, median age 16 years 4 months, median disease duration 3 years 10 months) and 21 age and gender-matched healthy controls and differentiated in vitro with macrophage-colony stimulating factor. Cells were treated with interferon gamma for 24 hours to upregulate HLA B, washed and then stimulated with lipopolysaccharide (LPS) alone (50 ng/mL) or LPS and tunicamycin (TM) (5 µg/mL), an inducer of the unfolded protein response. GMCSF was measured from the cell culture supernatants after 24 hours culture by luminex assay. Results: Levels of GMCSF at baseline were similar in patients and healthy controls [median 121.3 pg/mL (IQR 96.6–194.0 pg/mL) vs 157.1 pg/mL (124.2–203.3 pg/mL), p=0.1]. However, with LPS stimulation, MDMs from patients secreted significantly higher levels of GMCSF [median 1853 pg/mL (IQR 1206–3061 pg/mL) vs 1342 pg/mL (IQR 713.3–1797 pg/mL), p=0.0057]. On stimulation with TM in addition to LPS, GMCSF production was further enhanced in both patients and healthy controls [median 9027 pg/mL (IQR 4746–13961 pg/mL) vs 3834 pg/mL (IQR 1603–9158 pg/mL)] and remained significantly higher in patients (p=0.0096). To investigate the effect of the UPR, fold change in GMCSF was calculated for each sample between MDMs stimulated with LPS alone and MDMs stimulated with both LPS and TM. Median fold change in patients was 3.95 (IQR 1.54–5.47) and 2.36 (IQR 0.49–4.69) in healthy controls. Interestingly, MDMs from patients who were HLA B27 positive exhibited significantly higher median fold change in GMCSF with UPR induction compared to HLA B27 negative patients [4.14 (IQR 2.22–6.10) vs 1.33 (IQR 0.36–3.91), p=0.0098]. No associations were seen with different treatment regimes in the patient group. Conclusions: MDMs from patients with ERA produce significantly higher levels of GMCSF after stimulation compared to healthy controls and this is further enhanced by the UPR, especially in HLA B27 positive patients. These results potentially implicate GMCSF in the pathogenesis of ERA and thus further support the concept of GMCSF as a novel target for treatment in certain subgroups of patients. Reference: [1] Al-Mossawi MH, Chen L, Fang H, Ridley A, de Wit J, Yager N, et al. Unique transcriptome signatures and GM-CSF expression in lymphocytes from patients with spondyloarthritis. Nat Commun2017Nov 15;8(1):1510. Disclosure of Interest: None declared